Crystallization process in thin stoichiometric GeSbTe films - Claudio, D.; Laine, B.; Licea, O.; Morales-Sanchez, E.; Prokhorov, E.; Trapaga, G. (Functional Materials, 2005)
The crystallization kinetics of Ge₁Sb₂Тe₄ and Ge₂Sb₂Тe₅ films has been analyzed using results of impedance measurements, in which Bruggerman's effective medium approximation was employed, considering that the amorphous matrix contained inclusions of two different crystalline phases. To validate the predictions from analytical model, we compared those with experimental results obtained for Ge₁Sb₂Тe₄ and Ge₂Sb₂Тe₅ films. The proposed analytical model allows us to simulate similar transformation curves as those obtained from the experiments in different materials.